Adsorption and desorption kinetics of 60Co and 137Cs in fresh water rivers. (November 2015) - Fiengo Pérez, Fabricio; Sweeck, Lieve; Bauwens, Willy; Van Hees, May; Elskens, Marc
Abstract: Radionuclides released in water systems – as well as heavy metals and organic toxicants – sorb to both the suspended solid particles and the bed sediments. Sorption is usually represented mathematically by the distribution coefficient. This approach implies equilibrium between phases and instantaneous fixation (release) of the pollutant onto (from) the surface of the soil particle. However, empirical evidence suggests that for some radionuclides the fixation is not achieved instantaneously and that the reversibility of the process can be slow. Here the adsorption/desorption kinetics of 60 Co and 137 Cs in fresh water environments were simulated experimentally and later on modelled mathematically, while the influence of the most relevant factors affecting the sorption were taken into account. The experimental results suggest that for adsorption and the desorption more than 24 h are needed to reach equilibrium, moreover, It was observed that the desorption rate constants for 60 Co and 137 Cs lie within ranges which are of two to three orders of magnitude lower than the adsorption rate constants. Highlights: The Kd values and the adsorption and desorption kinetics of 60 Co increase with pH. Experiments show that 137 Cs is almost completely and irreversibly fixed on sediments. The kinetic model describes consistently the adsorption and desorption reactions.